Inheritance Development Patterns in Multiethnic Societies in Indonesia: Between Custom, Religion, and State - Elfia, Elfia; Nurus, Nurus Shalihin; Surwati, Surwati; Yan, Yan fajri; Mardiyah, Siti Mardiyah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study aims to analyze the patterns for developing inherited assets in multiethnic communities in Pasaman and Dharmasraya (West Sumatra) and Mandailing Natal and Panyabungan (North Sumatra). The research focuses on the interaction between customary, religious, and state laws in inheritance practices and their implications for social relations, family cohesion, and economic orientation. Using a qualitative comparative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis with inter-ethnic families. The research findings reveal three distinct patterns of heritage development. The collective-conservative pattern in Pasaman emphasizes family solidarity and asset preservation, while also reflecting internal power relations and potential conflicts of interest in decision-making. The customary-conservative pattern in Dharmasraya highlights the dominance of customary norms in heritage management, oriented toward social stability and cultural preservation, yet it can also reinforce traditional authority structures and symbolic subordination. Meanwhile, the individualistic-commercial pattern in Mandailing Natal prioritizes maximizing economic value and enhancing family economic mobility, but it may generate social differentiation and economic inequality among family members. These findings indicate that heritage development patterns are shaped not only by economic considerations but also by “ethnic logic” rooted in kinship structures, customary norms, and social relations. Across most locations, customary law remains the dominant framework, religious law provides moral legitimacy and distribution guidance, and state law is applied selectively. In conclusion, this study demonstrates that legal pluralism in Indonesia’s multi-ethnic context is not merely a normative reality, but also a socially chosen strategy.